1980
DOI: 10.1111/j.1365-2125.1980.tb01786.x
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol LA and ambulatory blood pressure.

Abstract: 1 The technique of continuous recording of intra-arterial blood pressure in ambulant hypertensives has been used to investigate the effects of a long-acting formulation ofpropranolol (propranolol LA). 2 Seven subjects with untreated essential hypertension were studied before and 2 months after commencing treatment with propranolol LA once daily in the morning, results showing that smooth control of blood pressure and heart rate occurred throughout 24 h. 3 Bicycle ergometry tests performed by these subjects dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1981
1981
1988
1988

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The mean steady-state plasma drug concentrations in the 15 patients in Group A after 4 weeks' treatment with LA propranotol 160 and 320 mg, were similar to those reported in European patients of greater average body weight and height (Mann et al, 1980). We conclude, first, that there seem to be no important differences in the pharmacokinetics or the effects on BP and HR of LA propranolol, in the usual dosage, between hypertensive Chinese in this study and European subjects as reported elsewhere (Mann et al, 1980 …”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The mean steady-state plasma drug concentrations in the 15 patients in Group A after 4 weeks' treatment with LA propranotol 160 and 320 mg, were similar to those reported in European patients of greater average body weight and height (Mann et al, 1980). We conclude, first, that there seem to be no important differences in the pharmacokinetics or the effects on BP and HR of LA propranolol, in the usual dosage, between hypertensive Chinese in this study and European subjects as reported elsewhere (Mann et al, 1980 …”
Section: Discussionsupporting
confidence: 62%
“…We conclude, first, that there seem to be no important differences in the pharmacokinetics or the effects on BP and HR of LA propranolol, in the usual dosage, between hypertensive Chinese in this study and European subjects as reported elsewhere (Mann et al, 1980 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Compliance in the treatment of hypertension is one of the most important problems (Cohn, 1974) (Watson et al, 1979a;Mann et al, 1980). Timolol taken once daily lowered BP over the 24 h, although the reduction was not statistically significant for a short period between 04.00 h and 09.00 h when 2 points for SBP and 4 points for DBP were not significantly reduced.…”
Section: Discussionmentioning
confidence: 99%
“…(1) the possibility of an antidepressant effect of yohimbine itself since a therapeutic role of noradrenergic function stimulation in the treatment of depression has been described (Puech, Lecrubier & Simon, 1979 Received December 31, 1980 EFFECT OF PROPRANOLOL LA ON AMBULATORY BLOOD PRESSURE We wish to comment on the conclusions drawn from the study of the effects of propranolol LA on ambulatory blood pressure recently reported by Mann et al (1980). Of the twelve previously untreated Group I patients, only seven were subsequently restudied; consequently, these represent a highly selected sub-group.…”
mentioning
confidence: 95%